Pakistan's failed gamble the battle of Laungewala - Shorey Anil (New Delhi Manas Publications, 2005)
The book describes not only the valour and sacrifice of the men under Chandpuri, but it also gives an insight into the battle through various 'dramatis personae', such as Lieutenant Dharam Vir who had taken out a patrol towards the border, which was the
Keywords: Indo-Pak war